Radiative processes in jets - Vila, Gabriela Soledad (2010)
Relativistic jets and collimated outflows are ubiquitous phenomena in astrophysical settings, from young stellar objects up to Active Galactic Nuclei. The observed emission from some of these jets can cover the whole electromagnetic spectrum, from radio to gamma-rays. The relevant features of the spectral energy distributions depend on the nature of the source and on the characteristics of the surrounding environment. Here the author reviews the main physical processes that command the interactions between populations of relativistic particles locally accelerated in the jets, with matter, radiation and magnetic fields. Special attention is given to the conditions that lead to the dominance of the different radiative mechanisms. Examples from various types of sources are used to illustrate these effects.